2018
DOI: 10.1063/1.5054842
|View full text |Cite
|
Sign up to set email alerts
|

Nanowires for energy: A review

Abstract: Semiconductor nanowires (NWs) represent a new class of materials and a shift from conventional two-dimensional bulk thin films to three-dimensional devices. Unlike thin film technology, lattice mismatch strain in NWs can be relaxed elastically at the NW free surface without dislocations. This capability can be used to grow unique heterostructures and to grow III-V NWs directly on inexpensive substrates, such as Si, rather than lattice-matched but more expensive III-V substrates. This capability, along with oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(73 citation statements)
references
References 190 publications
0
71
0
Order By: Relevance
“…These lead to an increase of the light confinement and photosensitivity 6 , features essential for applications such as photodetectors 7 , lasers 8 , solar cells 9 , photocatalysis 10 , etc. Additionally, the progress made in tuning the material properties during their synthesis led to the development of heterostructure nanowires with different architectures, such as axial, radial or branched 11 13 . Amidst them, radial core–shell heterostructure nanowires obtained using two semiconductors arranged in a type II (staggered gap) band alignment augmenting the charge carrier separation efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…These lead to an increase of the light confinement and photosensitivity 6 , features essential for applications such as photodetectors 7 , lasers 8 , solar cells 9 , photocatalysis 10 , etc. Additionally, the progress made in tuning the material properties during their synthesis led to the development of heterostructure nanowires with different architectures, such as axial, radial or branched 11 13 . Amidst them, radial core–shell heterostructure nanowires obtained using two semiconductors arranged in a type II (staggered gap) band alignment augmenting the charge carrier separation efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike thin-lms, the strain relaxation of nanostructures hinders defect formation because of their low dimensionality. 29 A large surface-to-volume ratio is also another advantage of nanostructures when it comes to PEC cells due to the increased surface area which can enhance light absorption and surface reactions. Faqrul A. Chowdhury et al recently reported on a PEC cell with vertically aligned InGaN nanosheets grown by MBE ( Fig.…”
Section: Physical Vapor Depositionmentioning
confidence: 99%
“…A considerable number of review papers are available on the incredibly rapid progress of such semiconductor nanowires and their diverse applications. [54][55][56][57] However, very few of them have considered the current status of WBG nanowires-based sensing devices with an emphasis placed on environmental monitoring applications. On the basis of these observations, this article provides a comprehensive review of the research activities focusing on the use of WBG semicon-ductor nanowires of SiC, group III-nitrides, and diamond for environmental monitoring applications.…”
Section: Introductionmentioning
confidence: 99%